Sistem Pendukung Keputusan Rekrutmen Staff Marketing Menggunakan Metode Analytical Hierarchy Process - Yudhistira, Aditia (Journal of Information Technology, Software Engineering and Computer Science (ITSECS), 2024)
The company's marketing staff recruitment process focuses on finding individuals who have strong communication skills, high creativity, and a deep understanding of the market and industry trends. The ideal candidate should be able to develop innovative marketing strategies to increase brand visibility and expand the company's market share. The decision support system (DSS) for marketing staff recruitment using the analytical hierarchy process (AHP) method is an application designed to assist HR managers or recruitment teams in making effective and efficient decisions related to marketing staff recruitment. The AHP method is used to evaluate criteria that are important in the recruitment process, as well as to compare prospective employees based on these criteria. By using AHP, DSS can assign relative weight to each criterion and alternative, thus enabling managers to make decisions based on structured and mature analysis. This DSS will help minimize errors in employee selection and improve the match between prospective employees and company needs, so as to improve the performance of the marketing team and the company's overall contribution. The ranking results found that Budi became the 1st best in marketing staff recruitment with a value of 2.170024213.